2018
DOI: 10.1007/s00063-018-0477-z
|View full text |Cite
|
Sign up to set email alerts
|

qSOFA score not predictive of in-hospital mortality in emergency patients with decompensated liver cirrhosis

Abstract: qSOFA does not predict in-hospital mortality, ICU admission or length of hospitalisation in patients with decompensated liver cirrhosis. Extension of qSOFA with a disease-specific component, the qSOFA-Na+, moderately increased the diagnostic ability of qSOFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
1
Order By: Relevance
“…ASB, asymptomatic bacteriuria; ICU, intensive care unit; UTI, urinary tract infection in specific populations, such as patients with haematological malignancies 27 or cirrhosis. 28,29 In our study, qSOFA was the only score associated with inhospital mortality by multivariate analysis. It is quite striking that a simple score such as qSOFA were the only prognostic score that had an association with in-hospital mortality, while APACHE II and SOFA, more complex scores designed to measure the severity of disease or track the rate of organ failure for patients admitted to intensive care units, did not show any association.…”
Section: Discussionmentioning
confidence: 46%
“…ASB, asymptomatic bacteriuria; ICU, intensive care unit; UTI, urinary tract infection in specific populations, such as patients with haematological malignancies 27 or cirrhosis. 28,29 In our study, qSOFA was the only score associated with inhospital mortality by multivariate analysis. It is quite striking that a simple score such as qSOFA were the only prognostic score that had an association with in-hospital mortality, while APACHE II and SOFA, more complex scores designed to measure the severity of disease or track the rate of organ failure for patients admitted to intensive care units, did not show any association.…”
Section: Discussionmentioning
confidence: 46%
“…Currently, the diagnosis of sepsis with the SOFA score to evaluate organ dysfunction in the setting of infection and the use of qSOFA to predict the severity and outcome of sepsis have been recommended by the Sepsis-3 consensus document. Müller et al[ 59 ] showed that qSOFA did not predict in-hospital mortality, intensive unit admission, or length of hospitalization in patients with decompensated cirrhosis. The application of sodium level to qSOFA (called qSOFA-Na + ) improved the diagnostic ability for identifying sepsis and mortality.…”
Section: Update On Prognostic Scoring Systems For Sepsis In Cirrhosismentioning
confidence: 99%
“…However, more verification was not yet made in the related subgroups of the emergency department patients having high mortality. Müller M et al detected that the qSOFA did not predict in-hospital mortality, intensive care unit or hospitalization period in the patients with decompensated liver cirrhosis in the study performed on 186 patients with liver cirrhosis [25]. In our study, it was detected that positive result of one of the qSOFA criteria increased the specificity by 86.00% in predicting the poor prognosis in the AP.…”
Section: Discussionmentioning
confidence: 40%